Protein Quality Control at the Mitochondrial Surface - den Brave, Fabian; Gupta, Arushi; Becker, Thomas (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria contain two membranes, the outer and inner membrane. The outer membrane fulfills crucial functions for the communication of mitochondria with the cellular environment like exchange of lipids via organelle contact sites, the transport of metabolites and the formation of a signaling platform in apoptosis and innate immunity. The translocase of the outer membrane (TOM complex) forms the entry gate for the vast majority of precursor proteins that are produced on cytosolic ribosomes. Surveillance of the functionality of outer membrane proteins is critical for mitochondrial function and biogenesis. Quality control mechanisms remove defective and mistargeted protein from the outer membrane as well as precursor proteins that clog the TOM complex. Selective degradation of single proteins is also an important mode to regulate mitochondrial dynamics and initiation of mitophagy pathways. Whereas inner mitochondrial compartments are equipped with specific proteases, the ubiquitin-proteasome system is a central player in protein surveillance on the mitochondrial surface. In this review, we summarize our current knowledge about the molecular mechanisms that govern quality control of proteins at the outer mitochondrial membrane.